Quantitative Live-Cell Ca2+ Imaging During Isotropic Cell Stretch - Schöler, Ulrike; Merten, Anna-Lena; Schürmann, Sebastian; Friedrich, Oliver (Cell Viability Assays (2nd Edt), 2023)
Cell viability of many cell types strongly relies on their ability to adjust to mechanical conditions and alterations. Cellular mechanisms for sensing and responding to mechanical forces and pathophysiological variations in these processes have become an emerging research field in recent years. An important signaling molecule involved in mechanotransduction as in many cellular processes is Ca2+. New experimental methods to probe cellular Ca2+ signaling live under conditions of mechanical stimulation facilitate new insights into previously overlooked aspects of mechanical regulation of cells. Here, we describe a protocol for using Ca2+ imaging in combination with a cell stretching device, the IsoStretcher. Cells grown on elastic membranes can be isotopically stretched in-plane, and their intracellular Ca2+ level can be accessed online on the single cell level using fluorescent calcium indicator dyes. We show a protocol for functional screening of mechanosensitive ion channels and related drug screenings using BJ cells, a foreskin fibroblast cell line that strongly reacts to acute mechanical stimulation.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Calcium imaging; Cell stretching; Image processing; IsoStretcher; Mechanobiology; Mechanosignaling; Mechanotransduction